(untitled) (Bangladesh Heart Journal, 2017)
Background: Increased Tpeak-to-end/QT ratio on 12 lead surface electrocardiogram (ECG) has been shown to be the predictor of arrhythmogenesis in various cardiac disorders. There is limited data regarding association of these two parameters with malignant ventricular arrhythmias (MVA) in acute ST-segment elevation myocardial infarction (STEMI) patients. Objectives: This study was conducted to evaluate association of increased Tpeak-to-end/QT ratio with MVAs in acute anterior STEMI. Methods: 178 patients with acute anterior STEMI admitted within 12 hours of onset of chest pain into the Coronary Care Unit, Department of Cardiology, National Institute of Cardiovascular Diseases, Dhaka, were enrolled from November 2015 to October 2016. Tpeak-to-end/QT ratio was calculated from surface ECG at the time of admission. The patients were divided into two groups, group I and II according to normal (?0.25) and increased Tpeak-to-end/QT ratio (>0.25). Each group was monitored for development of MVAs for the first 48 hours of myocardial infarction. Results: MVAs were significantly higher in group II than group I (19.5% vs 3.1%, p<0.001). Multivariate regression analysis showed significant association (p=0.002) of increased Tpeak-to-end/QT ratio with MVAs (Odds Ratio, 3.845).Receiver operating characteristic (ROC) curve analysis showed that Tpeak-to-end/QT ratio <0.25 had a negative predictive value of 96.88% for the prediction of MVAs. Conclusion: The study demonstrated that there was significant association of increased Tpeak-to-end/QT ratio with malignant ventricular arrhythmias in acute anterior STEMI patients. Thus analysis of 12 lead surface ECG on admission may help predict malignant ventricular arrhythmias in the first 48 hours of acute anterior myocardial infarction and close monitoring with prompt management may be ensured in high risk patients. Bangladesh Heart Journal 2017; 32(1) : 10-17